Sustainable Green Business Models in Rural Tourism for Economic Development: A Literature Review - Onan Marakali Siregar; Maulidina Maulidina; Andriansyah Andriansyah (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract:  Abstract: This literature review aimed to explore how sustainable green business models influence rural tourism and its contribution to economic development, emphasizing the importance of this topic in promoting long-term viability and resilience in rural communities. It focused on the critical elements of sustainable rural tourism, including infrastructure, community engagement, resource management, and economic collaboration. Utilizing a systematic review methodology grounded in the PRISMA framework, the study analyzes peer-reviewed literature from developing countries sourced from ScienceDirect, Emerald Insight, Taylor and Francis, and ProQuest. From an initial dataset of 20,433 records, 21 high-quality studies were selected based on their relevance to the review objectives. The analysis revealed challenges, such as balancing economic growth with environmental conservation and maintaining rural authenticity while identifying opportunities for economic diversification and support for small businesses. This review advocated a holistic approach integrating eco-friendly practices, community involvement, and technological advancement to achieve sustainable economic growth, environmental preservation, and cultural integrity in rural tourism.